(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Due to high transportation costs in open pit mines, various optimization methods have been developed in this field. Using these methods is much simpler in homogeneous fleets than heterogeneous fleets and it is better to use metaheuristic methods in heterogeneous systems. The number of trucks allocated to each loading device in an iron ore mine was determined in this study using the imperialist competitive algorithm, and with the aim of increasing production in a heterogeneous environment. , Then, to determine the amount of production according to the distribution functions which related to the time cycles, the transportation fleet was simulated and the problem was solved. Iron ore production in the simulated model was increased by 4.4% and the waste rock by 4.1%. In this optimization process, there was also a better control over the production amount of iron containing the intrusive element of phosphor.